KEBERMAKNAAN HIDUP LANSIA DI PANTI WREDA BEKASI - Purwantini, Lucky (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2014)
This study is aims to understand the meaning of life of the elderly who live in nursing homes. Meaning of life is something that is meaningful in individu that causes him or herself to live their life. In an old age, with a variety of events and experiences that have been passed, it is expected that those individu would have a meaning of life. This study used a qualitative method of data collection in the form of interviews and observations. From the result of interview and observation it is found that the elderly living in nursing homes in Bekasi have not find their meaning of life yet. They are still in the stage of the process to find the meaning of life